The Qur’ans of the Spanish Moriscos and the Tatars of the Grand Duchy of Lithuania: Drawing Comparisons and Tracing Patterns - Katarzyna K. Starczewska (Lietuvos Istorijos Studijos)
This paper is aimed at presenting a preliminary comparative study of the Qur’anic translations produced by two autochthonous European Muslim communities: Spanish Mudéjars (Muslims who remained in the Iberian Pen- insula after the Christian reconquest) and Moriscos (former Muslims forced to convert to Christianity) and, on the other side of Europe, the Tatars of Grand Duchy of Lithuania (GDL). The framework for this comparison is provided by some basic facts: over the span of two centuries, in the case of the Morisco pop- ulation (starting with the conquest of Granada in 1492, until the expulsion of the Moriscos in 1609)1, and three centuries in that of the Tatars of the GDL (17th to 19th centuries), their literary production was exclusively hand-written. Both groups preserved their Muslim religiosity but, with some erudite exceptions, had only scarce knowledge of Arabic, the holy language of Qur’anic revelation. Moreover, without having access to one another’s culture, both Moriscos and the Tatars of the GDL adapted the Arabic alphabet to their vehicular languag- es, Romance and Slavic respectively2. Thanks to this adaptation strategy, they maintained the sacred aspect of their writings and were able to translate the Qur’an into a language they fully understood. However, in spite of these strik- ing similarities between the two groups, there were also notable differences. While the Tatars of the GDL were granted full religious freedom, the Moriscos were heavily persecuted for any signs of adherence to Islam. In order to shed more light on the phenomenon of European Muslim cultures, in this paper I will present various manuscript examples of these groups’ Qur’anic translations, and draw some preliminary conclusions regarding the information that can be retrieved from this kind of sources.